Action Learning Sets: The case for running them online - Bird, Len (Proceedings of the International Conference on Networked Learning, 2002)
This paper develops an argument for using asynchronous online computer mediated conferencing (CMC) to facilitate the action learning set process. It starts with a definition of action learning and then traces the roots of action learning back to the philosophical position of social constructionism. From this analysis the paper establishes that the key feature of action learning is the promotion of reflexivity and the social construction of knowledge through language. The paper then examines the literature on online communication to answer the question, "can an action learning set community be created via a text-only CMC?" Having examined competing responses to this question the paper concludes by considering the main challenge to the argument, (i.e the loss of copresence) and the role of the online facilitator as an ‘online discourse analyst’.